ASSESSING PERFORMANCE USING SCORING RUBRICS: AN OVERVIEW - Made Frida Yulia (Kajian Linguistik dan Sastra, 2005)
One of the Strategies of Contextual Teaching and Learning is authentic assessment, which can provide valid and accurate information about what students really know and are able to do, or about the quality of educational programs. One of its forms is performance assessment. It requires students to demonstrate the application of knowledge to a particular context. The prevailing philosophy of performance assessment is that it provides ways to improve achievement, demonstrate exactly what a student does or does not understand, relate learning experiences to instruction, and combine assessment with teaching. Despite the benefits, some teachers are hesitant to implement it because they do not have enough knowledge about how to assess a student's performance properly. Since in performance assessment there are degrees to which a student is successful or unsuccessful, the performance should be evaluated in such a way that it allows teachers to consider those degrees, that is by creating rubrics. This paper attempts at discussing basic steps in implementing performance assessment in general and developing scoring rubrics in particular.Key words: performance, assessment, scoring rubric, analytic, and holistic